P3 1 Energy of the Empire - Purushu, Pooja; Alcock, Ellie; McNaughton, Tom (Physics Special Topics, 2024)
This paper seeks to explore the blaster Princess Leia uses in Star Wars: Episode IV - A New Hope during the rescue scene aboard the Death Star. We aim to analyse the energy required to vaporise the grate based on its size and material. We assume the grate is a metal material such as steel and the dimensions are 3 feet by 3 feet. The study explores thermodynamic principles and material properties to estimate the energy delivered by Leia’s blaster, which is calculated to be 22.7 GW.